Preference for modernization is universal, but expected modernization trajectories are culturally diversified: A nine‐country study of folk theories of societal development. Issue 4 (30th March 2022) - Krys, Kuba; Capaldi, Colin A.; Uchida, Yukiko; Cantarero, Katarzyna; Torres, Claudio; Işık, İdil and Yeung, Victoria Wai Lan and Haas, Brian W. and Teyssier, Julien and Andrade, Laura and Denoux, Patrick and Igbokwe, David O. and Kocimska‐Zych, Agata and Villeneuve, Léa and Zelenski, John M.
Abstract : Cultural sensitivity in societal development has been advocated for since at least the 1960s but has remained understudied. Our goal is to address this gap and to investigate folk theories of societal development. We aimed to identify both universal and culturally specific lay beliefs about what constitutes good societal development. We collected data from 2, 684 participants from Japan, Hong Kong (China), Poland, Turkey, Brazil, France, Nigeria, the USA, and Canada. We measured preferences for 28 development aims. We used multidimensional scaling, analysis of variance, and pairwise comparisons to identify universal and country‐specific preferences. Our results demonstrate that what people understand as modernization is fairly universal across countries, but specific pathways of development and preferences towards these pathways tend to vary between countries. We distinguished three facets of modernization—foundational aims (e.g., trust, economic development), welfare aims (e.g., poverty eradication, education), and inclusive aims (e.g., openness, gender equality)—and incorporated them into a folk meta‐theory of modernization. In all nine countries, the three facets of modernization were preferred more than conventional aims (e.g., military, demographic growth). We propose a method of implementing our findings into a culturally sensitive modernization index.